A Multi-Role Web-Based Customer Relationship Management (CRM) Information System Using the Agile Method at Telkom Witel Lampung–Bengkulu - Muhammad Ikhsan; Intan Nur Laila; Rahayu Indah Lestari; Anindita Tri Mulia; Allwine (STMIK Methodist Binjai, 2026)
This study discusses the development of a web-based Customer Relationship Management (CRM) Information System at PT Telekomunikasi Indonesia, Tbk Witel Lampung-Bengkulu by integrating three main roles: Admin, Government Service, and Shared Service General Support. The main problem identified is that user data, regional data, project opportunities, marketing activities, customer data, customer interactions, and payment monitoring were still mostly managed manually using Microsoft Excel, which could cause data duplication, reporting delays, and input errors. This study applied the Agile method through planning, design, development, testing, deployment, and review stages. The system was developed using PHP with the Laravel framework, MySQL database, and Bootstrap to create a responsive user interface. The developed features include login, user management, regional data management, dashboard, Government Service project opportunity management, marketing activity records, customer data, interaction history, payment monitoring, filters, import, export, and user profile. System testing was conducted using Black Box Testing and User Acceptance Testing to ensure that each function met user requirements. The resulting system integrates administration, government sales, and customer collection processes into one platform, making data more centralized, monitoring faster, and reporting more accurate and well documented.